Tinjauan Penyaluran Dana BSPS di Desa Tusan, Kecamatan Banjarangkan, Kabupaten Klungkung - Juniartini, Ni Luh Putu (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
A decent house is everyone's dream, but in reality, there are still many houses that are still not up to standard. In Tusan Village, Banjarangkan District, Klungkung Regency through the BSPS PUPR program, 50 houses were allocated assistance. Procedurally, these houses are houses that have very unfit verification. Based on data from village officials and proposals that have been required, the recipient of the assistance must go through the submission process according to the rules. In the field process, there are three crucial constraints in broad outline and require intensive assistance solutions so that the BSPS program runs according to the initial planning. The synergy between the community, village officials, and the government is also needed in this process so that significant obstacles can be resolved in accordance with applicable regulations. In the end, this program can run on target and can also be enjoyed by the community in Tusan Village.